Noise induced hearing loss and factors affecting It among the vector control workers in Sarawak - Musalnizan, Mustalkah (Universiti Malaysia Sarawak (UNIMAS), 2013)
Noise Induced Hearing Loss (NIHL) is known as the most common occupational disease in industrial countries. In Malaysia, Hearing Conservation Programme (HCP) was introduced under Noise Regulation 1989 (Factories and Machinery (Noise Exposure) Regulations, 1989) and it is to protect workers from noise exposure and hence preventing NIHL. Cases of NIHL investigated by Department Occupational Safety and Health (DOSH) had increased from 120 cases in 2007 to 427 cases in 2009 for all categories except for military personnel. However, there is no established data of NIHL among medical personnel in Sarawak)This study aims to determine the proportion of noise induced hearing loss (NIHL) among vector control worker and factors associated with NIHL. This was a retrospective study to evaluate the medical record of workers who involved in vector control using fogging machine who attended occupational health clinic in Klinik Kesihatan Kota Sentosa. The total of 166 records with PTA (Pure Tone Audiometry) result between January 2007 and December 2012 were obtained and collected using the checklist. The proportion of NIHL was 56% among this group of workers. Noise Induced Hearing Loss was significantly associated with the age group of 40 years and older, being married, duration exposed to noise 9 years and above, with personal and family medical history and specific medical symptoms (p<0.05). Although providing and usage of Hearing Protective Device (HPD) did not show significant result, but it is proven by many other studies. Therefore, education towards the importance of proper usage of HPD among workers must be implemented thoroughly.